(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Biru Y, Gibru A, Temesgen Z, Hunde K, Fekensa T. 2022. Zootherapeutic animals used by Awi, Gamo, and Konta communities in Amhara and Southern Regions of Ethiopia. Asian J Ethnobiol 5: 84-91. The use of animals and animal products in traditional medicine is less explored than that of plant-based medication. And hence, this pilot study is aimed to assess the role of zootherapeutic animals in traditional medicine among Awi, Gamo, and Konta communities, Ethiopia. Data were collected from December 2020 to March 2021 using a semi-structured questionnaire, focus group discussions, and field observations. A total of 90 informants and 37 group discussants were included in the study. We calculated the use value (UV) and relative frequency of citation (RFC) of animals used in traditional medicine. A binary Logistic Regression model using SAS (9.0) was used to identify the major factors that affected respondents’ knowledge about the importance of animal-based traditional medicine. Overall, we documented 20 medicinal animals having ethnozoological importance in treating nearly 23 human diseases. Out of the 20 vertebrate species used, mammals comprised 70%, followed by birds, 20%. Among the recorded animal species, hyena, porcupine, and bushbuck were commonly reported medicinal animals in the study areas. Meat, skin, and blood were the most frequently used animal products by local communities, with a pooled RFC of 0.48, 0.28, and 0.13, respectively. Asthma, protection from the evil eye, and broken bone were most commonly treated diseases using animal-based therapeutics. The binary logistic regression model revealed that age (?2=10.53; df=3; P=0.01) and region (?2=5.11; df=1; P=0.02) of respondents significantly affected ethnozoological knowledge of respondents. This study confirmed that the sampled communities have rich ethnozoological knowledge concerning the use of traditional medicine. Therefore, further in-depth studies involving traditional healers are recommended to clearly understand the role of wild animals in traditional medicine and design conservation options for the threatened medicinal animals.